The transcription of the main gene associated with Treacher–Collins syndrome (TCOF1) is regulated by G-quadruplexes and cellular nucleic acid binding protein (CNBP) - Gil Rosas, Mauco Lucas (2024)
Treacle ribosome biogenesis factor 1 (TCOF1) is responsible for about 80% of mandibular dysostosis(MD) cases. We have formerly identifed a correlation between TCOF1 and CNBP (CCHC-type zincfnger nucleic acid binding protein) expression in human mesenchymal cells. Given the establishedrole of CNBP in gene regulation during rostral development, we explored the potential for CNBP tomodulate TCOF1 transcription. Computational analysis for CNBP binding sites (CNBP-BSs) in theTCOF1 promoter revealed several putative binding sites, two of which (Hs791 and Hs2160) overlapwith putative G-quadruplex (G4) sequences (PQSs). We validated the folding of these PQSs measuringcircular dichroism and fuorescence of appropriate synthetic oligonucleotides. In vitro studiesconfrmed binding of purifed CNBP to the target PQSs (both folded as G4 and unfolded) with Kdvalues in the nM range. ChIP assays conducted in HeLa cells chromatin detected the CNBP binding toTCOF1 promoter. Transient transfections of HEK293 cells revealed that Hs2160 cloned upstream SV40promoter increased transcription of downstream frefy luciferase reporter gene. We also detected aCNBP-BS and PQS (Dr2393) in the zebrafsh TCOF1 orthologue promoter (nolc1). Disrupting this G4in zebrafsh embryos by microinjecting DNA antisense oligonucleotides complementary to Dr2393reduced the transcription of nolc1 and recapitulated the craniofacial anomalies characteristic ofTreacher Collins Syndrome. Both cnbp overexpression and Morpholino-mediated knockdown inzebrafsh induced nolc1 transcription. These results suggest that CNBP modulates the transcriptionalexpression of TCOF1 through a mechanism involving G-quadruplex folding/unfolding, and that thisregulation is active in vertebrates as distantly related as bony fsh and humans. These fndings mayhave implications for understanding and treating MD.